Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

-7(n - 2) + 2n = -5(n + 6)

Sagot :

Given the expression below

[tex]-7(n-2)+2n=-5(n+6)[/tex]

To find n

Open the brackets

[tex]\begin{gathered} -7(n-2)+2n=-5(n+6) \\ -7n+14+2n=-5n-30 \\ -7n+2n+14=-5n-30 \\ -5n+14=-5n-30 \end{gathered}[/tex]

Collect like terms

[tex]\begin{gathered} -5n+14=-5n-30 \\ -5n-(-5n)=-30-14 \\ 0\ne-44 \end{gathered}[/tex]

Since, the sides are not equal,

Hence, there is no solution